2010
DOI: 10.1111/j.1476-5381.2009.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of kinin B1 and B2 receptors in the scratching behaviour induced by proteinase‐activated receptor‐2 agonists in mice

Abstract: Background and purpose: Activation of the proteinase-activated receptor-2 (PAR-2) induces scratching behaviour in mice. Here, we have investigated the role of kinin B1 and B2 receptors in the pruritogenic response elicited by activators of PAR-2. Experimental approach: Scratching was induced by an intradermal (i.d.) injection of trypsin or the selective PAR-2 activating peptide SLIGRL-NH2 at the back of the mouse neck. The animals were observed for 40 min and their scratching response was quantified. Key resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Since PAR-3 does not evoke scratching in mice, only PAR-2 appears to mediate cutaneous itch directly, through a histamine-independent mechanism72. Activation of PAR-2 with tryptase or PAR-2-Activating Peptides (APs) elicits scratching in mice that is not blocked by antihistamines27,7278. Interestingly, c-fos+ neurons observed in the superficial dorsal horn after a PAR-2-AP injection were located in an anatomically distinct region compared with c-fos+ neurons after histamine injection79.…”
Section: Introductionmentioning
confidence: 99%
“…Since PAR-3 does not evoke scratching in mice, only PAR-2 appears to mediate cutaneous itch directly, through a histamine-independent mechanism72. Activation of PAR-2 with tryptase or PAR-2-Activating Peptides (APs) elicits scratching in mice that is not blocked by antihistamines27,7278. Interestingly, c-fos+ neurons observed in the superficial dorsal horn after a PAR-2-AP injection were located in an anatomically distinct region compared with c-fos+ neurons after histamine injection79.…”
Section: Introductionmentioning
confidence: 99%
“…The intradermal administration of deoxycholic acid to rats, for example, activates kallikreins to generate bradykinin and stimulate B 2 R signaling (Hayashi and Majima, 1999). The role of B 1 R and B 2 R activity in PAR 2 -dependent pruritus has also been investigated and suggests that kinin receptors function downstream of protease-induced pruritic responses (Costa et al, 2010). Although the bile acidbradykinin system has not been clearly defined, TRPV1 sensitization was recently demonstrated to contribute to liver disease-induced itch and is predicted to play a major role, potentially via receptors for bradykinin, histamine, serotonin, or PAR 2 (Belghiti et al, 2013).…”
Section: A the G Protein-coupled Receptor-transient Receptor Potentimentioning
confidence: 99%
“…One study also reported that mice which overexpressed epidermal KLK7 displayed massive itchy behavior [20]. Another study demonstrated that trypsin-induced scratching behavior in mice was inhibited by a PAR-2 blocking peptide, suggesting the role of serine protease/PAR-2 signaling in pruritus [21, 22]. PAR-2 is reported to interact synergistically with transient receptor potential (TRP) vanilloid type 1 (TRPV1), which belongs to the superfamily of TRP channels, thereby amplifying itch sensation.…”
Section: Par: Protease Activated Receptorsmentioning
confidence: 99%